’Think different’ to prevent extinction. Connecting Gregory Bateson’s Cybernetic Epistemology with Posthumanism - Palmer, Hugh (Murmurations: Journal of Transformative Systemic Practice, 2022)
Gregory Bateson (1904-1980) left a stark warning to humanity; either change how we think or face extinction. He warned that three drivers are leading us to catastrophe; our reliance upon ever developing technology, population increase and the way we think. Bateson offered what he termed a “cybernetic epistemology” as an alternative way of thinking, and I will offer some thoughts about how this might be made more accessible to help us find a route out of the panmorphic crisis described by Simon (2021) of multiple threats to our existence. As part of the discussion, I will outline the concepts of conscious purpose, dualistic thinking, and other Batesonian ideas, including his understanding of “mind” and of schismogenesis, with the hope of encouraging the changes to our thinking that Bateson hoped we might make. I will connect with more recent posthumanist writers who have been directly or indirectly influenced by Bateson and identify common areas of concern, and I suggest that much posthumanist discourse is remarkably similar to Bateson’s cybernetic epistemology.